PENGARUH EFEKTIVITAS ADMINISTRASI PERPAJAKAN TERHADAP REALISASI POTENSI KEWAJIBAN PAJAK PADA WAJIB PAJAK UMKM DI INDONESIA - Rangga Kurniawan; Muhammad Fatkhur Rozaq; Nabila Tazqia Azzahra; Taufik Arif Fadhilah; Anne Tonthawi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the influence of tax administration effectiveness on the realization of tax liability potential among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The MSME sector serves as a cornerstone of the national economy; however, it still faces a significant gap between potential and actual tax revenue due to low literacy and administrative hurdles. The methodology employs a quantitative approach with data analysis conducted through Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS 4.1.1.8 software. Hypothesis testing results indicate that tax administration effectiveness has a positive and significant impact on the realization of MSME tax liability potential, with a path coefficient of 0.620 and a T-Statistic value of 9.089. The administration effectiveness variable explains 38.4% of the variation in MSME tax potential realization. These findings confirm that system modernization through data integration (NIK-NPWP) and the Coretax system is crucial in reducing underreporting practices and enhancing voluntary compliance. The study suggests that tax authorities should continue optimizing digital services while mitigating technical obstacles and improving tax literacy for MSME actors in remote areas.